Tuning a ménage à trois: Co‐evolution and co‐adaptation of nuclear and organellar genomes in plants. (30th January 2013) - Greiner, Stephan; Bock, Ralph
Abstract Plastids and mitochondria arose through endosymbiotic acquisition of formerly free‐living bacteria. During more than a billion years of subsequent concerted evolution, the three genomes of plant cells have undergone dramatic structural changes to optimize the expression of the compartmentalized genetic material and to fine‐tune the communication between the nucleus and the organelles. The chimeric composition of many multiprotein complexes in plastids and mitochondria (one part of the subunits being nuclear encoded and another one being encoded in the organellar genome) provides a paradigm for co‐evolution at the cellular level. In this paper, we discuss the co‐evolution of nuclear and organellar genomes in the context of environmental adaptation in species and populations. We highlight emerging genetic model systems and new experimental approaches that are particularly suitable to elucidate the molecular basis of co‐adaptation processes and describe how nuclear‐cytoplasmic co‐evolution can cause genetic incompatibilities that contribute to the establishment of hybridization barriers, ultimately leading to the formation of new species.